Development of water quality model for Sg. Tebrau using QUAL2K - Zainudin, Zaki; Abd Rahman, Norazah; Abdullah, Norizan; Mazlan, Nurul Fadillah (Asian Network for Scientific Information, 2010)
Tebrau River starts in Senai and ends in the Straits of Johor and has been categorized as most polluted river in Malaysia. It has been classified as class III river water quality based on the Interim National Water Quality Standard (INWQS) with the average value of Water Quality Index (WQI) of 59. This study was focussed on simulating the effect of the pollution from industrial area to Tebrau River Basin by using QUAL2K which is the modenization version of QUAL2E. This water quality model involved in simulates two primary parameters which are Biochemical Oxygen Demand (BOD) and Ammoniacal Nitrogen (AN). It has been found out that QUAL2K model can be used as an outstanding tool in managing the river basin.